Lactate regulates pathological cardiac hypertrophy via histone lactylation modification - Zhao, Shuai‐Shuai; Liu, Jinlong; Wu, Qi‐Cai; Zhou, Xue‐Liang (Journal of cellular and molecular medicine, 2024)
Under the long‐term pressure overload stimulation, the heart experiences embryonic gene activation, leading to myocardial hypertrophy and ventricular remodelling, which can ultimately result in the development of heart failure. Identifying effective therapeutic targets is crucial for the prevention and treatment of myocardial hypertrophy. Histone lysine lactylation (HKla) is a novel post‐translational modification that connects cellular metabolism with epigenetic regulation. However, the specific role of HKla in pathological cardiac hypertrophy remains unclear. Our study aims to investigate whether HKla modification plays a pathogenic role in the development of cardiac hypertrophy. The results demonstrate significant expression of HKla in cardiomyocytes derived from an animal model of cardiac hypertrophy induced by transverse aortic constriction surgery, and in neonatal mouse cardiomyocytes stimulated by Ang II. Furthermore, research indicates that HKla is influenced by glucose metabolism and lactate generation, exhibiting significant phenotypic variability in response to various environmental stimuli. In vitro experiments reveal that exogenous lactate and glucose can upregulate the expression of HKla and promote cardiac hypertrophy. Conversely, inhibition of lactate production using glycolysis inhibitor (2‐DG), LDH inhibitor (oxamate) and LDHA inhibitor (GNE‐140) reduces HKla levels and inhibits the development of cardiac hypertrophy. Collectively, these findings establish a pivotal role for H3K18la in pathological cardiac hypertrophy, offering a novel target for the treatment of this condition.